Thoughts on Sensitivity Analysis and Uncertainty Propagation Methods with Respect to the Prompt Fission Neutron Spectrum Impact on Critical Assemblies - Rising, M.E. (Nuclear data sheets, 2015)
The prompt fission neutron spectrum (PFNS) uncertainties in the n+239Pu fission reaction are used to study the impact on several fast critical assemblies modeled in the MCNP6.1 code. The newly developed sensitivity capability in MCNP6.1 is used to compute the keff sensitivity coefficients with respect to the PFNS. In comparison, the covariance matrix given in the ENDF/B-VII.1 library is decomposed and randomly sampled realizations of the PFNS are propagated through the criticality calculation, preserving the PFNS covariance matrix. The information gathered from both approaches, including the overall keff uncertainty, is statistically analyzed. Overall, the forward and backward approaches agree as expected. The results from a new method appear to be limited by the process used to evaluate the PFNS and is not necessarily a flaw of the method itself. Final thoughts and directions for future work are suggested.